Associations of Matrix Metalloproteinase-9 and Tissue Inhibitory Factor-1 Polymorphisms With Parkinson Disease in Taiwan. Issue 5 (February 2016) - Chen, Yi-Chun; Wu, Yih-Ru; Mesri, Mina; Chen, Chiung-Mei
Abstract : Abstract: Matrix metalloproteinases (MMPs) function in the degradation of extracellular matrix and are considered to play a role in the pathogenesis of neurodegenerative diseases including Parkinson disease (PD). MMPs activities are modulated by tissue inhibitors of metalloproteinases (TIMPs). This study examined whether the genetic polymorphisms of MMP-3, gelatinase ( MMP-2 and MMP-9 ), TIMP-2, and TIMP-1 were associated with PD in Taiwan. A total of 359 PD patients and 332 controls were enrolled. The candidate genetic variants included MMP-2 rs2285053 (−735 C > T), MMP-3 rs3025058 (−1171 5A > 6A), MMP-9 rs3918241 (−1831 T > A), rs17576 (G > A, R279Q), and rs3787268 (G > A, intron), TIMP-1 rs4898 (T > C, F124F), and TIMP-2 rs7503607 (−269 G > T). Associations were tested by logistic regression, adjusted with gender and age at onset. Minor allele frequency of TIMP-1 rs4898 (36.0%) was significantly lower in the male PD patients than in the male controls (51.2%) (χ 2 test, P  = 0.004). When adjusted with gender and age at onset, MMP-9 rs17576 AA genotype was associated with PD susceptibility in a recessive fashion (odds ratios [OR] = 2.28, 95% confidence intervals [95% CI] = 1.12–4.62, P  = 0.02). In males, TIMP-1 rs4898 C allele was associated with a protective effect on PD (OR = 0.75, 95% CI = 0.60–0.94, P  = 0.014). We did not find association between the examined genetic variants of MMP-2, MMP-3, and TIMP-2 and PD susceptibility. This is the first study that demonstrated a protective effect of TIMP-1 rs4898 C allele on male PD and a modest association of MMP-9 rs17576 AA genotype with PD susceptibility in the Taiwan population. Further replication is needed for confirmation.